Pengaruh Keselamatan dan Kesehatan Kerja dan Komunikasi Interpersonal terhadap Kepuasan Kerja Karyawan PT PLN (Persero) ULP Rivai - Dimas Prayoga; Zunaidah Zunaidah; Yomeini Margareth; Yos Karimudin; Nia Meitisari (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of Occupational Safety and Health (OSH) and interpersonal communication on the job satisfaction of employees at PT PLN (Persero), Rivai Customer Service Unit (ULP), Palembang City. The research employed a quantitative approach using a causal research design. Data were collected by distributing questionnaires to employees of PT PLN (Persero), Rivai Customer Service Unit (ULP), Palembang City. Out of a population of 65 employees, a final sample of 50 respondents meeting the purposive sampling criteria was analyzed.  The data analysis techniques used included the classical assumption test, statistical analysis, and hypothesis testing. The results indicate that, partially, Occupational Safety and Health (OSH) and interpersonal communication have a positive and significant effect on employee job satisfaction. These findings suggest that the effective implementation of Occupational Safety and Health (OSH) practices, along with effective interpersonal communication, can improve employee job satisfaction. This study implies the crucial need for periodic OSH audits in high-risk operational areas and the reinforcement of tactical communication practices (pre-task safety briefings) to minimize workplace accidents and improve employee job satisfaction.